“Is Selangor in deep water?”: a corpus-driven account of air/water in the Malaysian Hansard Corpus (MHC) - Norsimah Mat Awal,; Azhar Jaludin,; Anis Nadiah Che Abdul Rahman,; Imran Ho Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Air or its English equivalent ‘water’ is very important in our everyday life so much so that when the tap runs dry, it even made it as one of the topics debated by politicians. This paper looks at the issues that surround air/water in Malaysian Parliamentary debates by specifically focusing its relation to the state of Selangor. The air/water related issues were examined based on the collocates of air and Selangor in the Malaysian Hansard Corpus (MHC) from Parliament 1 (P1) to Parliament 13 (P13). The findings show that air is consistently present as one of the collocates of Selangor from Parliament 4 (P4) to Parliament 13 (P13). However, air started to show an upward trend starting in Parliament 7 (P7) and continued to Parliament 13 (P13). The recurring issues during those periods are the never-ending water-related problems and the steps taken by the government to overcome the problems. In P7 and P8, the focus is on the source of water as it collocates with pembersihan logi air (water treatment plant) and kawasan tadahan air (water catchment area). In Parliament 10, Parliament 11, Parliament 12 and Parliament 13 the recurring issue with air and Selangor is penyaluran air mentah (the transfer of raw water) from the neighbouring state Pahang to Selangor. Another issue observed is penstrukturan air (restructuring) of water supply and services which was first observed in Parliament 12 and continues to Parliament 13. Thus, by focusing on the collocates of air this corpus-driven account has managed to show the trend of the parliamentary debates in relation to air and Selangor. Therefore, parliamentary debates where various issues of national interest are often raised offer opportunities for more critical analysis of issues that are important to the public.